2017
DOI: 10.1016/j.schres.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported sleep disturbances associated with procedural learning impairment in adolescents at ultra-high risk for psychosis

Abstract: Sleep disturbance contributes to impaired procedural learning in schizophrenia, yet little is known about this relationship prior to psychosis onset. Adolescents at ultra high-risk (UHR; N = 62) for psychosis completed the Pittsburgh Sleep Quality Index (PSQI) and a procedural learning task (Pursuit Rotor). Increased self-reported problems with sleep latency, efficiency, and quality were associated with impaired procedural learning rate. Further, within-sample comparisons revealed that UHR youth reporting bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…First, these results continue to support that the clinical staging model and in particular our allocation of participants to different stages is a good fit in that the more symptomatic individuals are, the more they may have sleep issues. Secondly, they support earlier evidence that sleep disruption is present in the early stages of illness when symptoms are sub-threshold (Castro et al, 2015;Grierson et al, 2018;Lunsford-Avery et al, 2017;Poe et al, 2017;Ruhrmann et al, 2010;Zanini et al, 2013). Thirdly, the clinical implications of these results are that for youth who may be at risk sleep is an important factor that may need to be assessed.…”
Section: Discussionsupporting
confidence: 80%
“…First, these results continue to support that the clinical staging model and in particular our allocation of participants to different stages is a good fit in that the more symptomatic individuals are, the more they may have sleep issues. Secondly, they support earlier evidence that sleep disruption is present in the early stages of illness when symptoms are sub-threshold (Castro et al, 2015;Grierson et al, 2018;Lunsford-Avery et al, 2017;Poe et al, 2017;Ruhrmann et al, 2010;Zanini et al, 2013). Thirdly, the clinical implications of these results are that for youth who may be at risk sleep is an important factor that may need to be assessed.…”
Section: Discussionsupporting
confidence: 80%
“…evidence has also shown that circadian disturbances are predictive of future psychosis symptom severity in groups at risk for bipolar disorder and psychosis (Castro et al, 2015;Lunsford-Avery et al, 2017). More specifically, a recent study with ultra-high risk participants found that increased fragmentation of circadian rest-activity rhythms, reduced daytime activity, increased daytime activity variability, and later nocturnal rest time at baseline were associated with the severity of psychosis symptoms and functioning at a one year follow-up (Lunsford-Avery et al, 2017).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…These disturbances in sleep are related to increased concurrent psychosis symptoms, poorer psychosocial functioning, cognitive deficits (i.e., impaired procedural learning), and sleep-related neural abnormalities (i.e., thalamus reductions) (Lunsford-Avery et al, Under Review; Lunsford-Avery et al, 2015; Lunsford-Avery et al, 2013; Poe et al, In Press). Perhaps most importantly, self-reported and actigraphic-measured sleep disturbances at clinical intake predict increased positive symptom severity over a 1-year period among CHR adolescents (Lunsford-Avery et al, 2015), suggesting potential risk markers for psychosis onset.…”
Section: Introductionmentioning
confidence: 99%